2015
DOI: 10.1016/j.jns.2015.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Blood circulating microparticle species in relapsing–remitting and secondary progressive multiple sclerosis. A case–control, cross sectional study with conventional MRI and advanced iron content imaging outcomes

Abstract: Background Although multiple sclerosis (MS) is thought to represent an excessive and inappropriate immune response to several central nervous system (CNS) autoantigens, increasing evidence also suggests that MS may also be a neurovascular inflammatory disease, characterized by endothelial activation and shedding of cell membrane microdomains known as ‘microparticles’ into the circulation. Objective To investigate the relationships between these endothelial biomarkers and MS. Methods We examined the relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
0
18
2
Order By: Relevance
“…Research in the field of MP biology has gained tremendous attention over the past decade with MPs being found to be significantly increased in several diseases including MS (10), AD (27), stroke (28), coronary artery disease (29), and type 2 diabetes (4) to name only a few. Consequently, MPs have become useful biomarkers of many diseases, which not only have diagnostic and prognostic value, but also provide mechanistic insights (1, 30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research in the field of MP biology has gained tremendous attention over the past decade with MPs being found to be significantly increased in several diseases including MS (10), AD (27), stroke (28), coronary artery disease (29), and type 2 diabetes (4) to name only a few. Consequently, MPs have become useful biomarkers of many diseases, which not only have diagnostic and prognostic value, but also provide mechanistic insights (1, 30).…”
Section: Discussionmentioning
confidence: 99%
“…EC-derived microparticles (“EMPs”) are constitutively released at low levels under normal physiological conditions, with the rate and magnitude of EMP release increasing during endothelial inflammatory activation or apoptosis (8). Several recent studies analyzing circulating MPs in plasma and serum samples have implicated MPs in the pathology of neurodegenerative, neurovascular and inflammatory diseases including stroke (9), multiple sclerosis (MS) (10) and Alzheimer's disease (AD) (11, 12). Apically released EMPs have widely been reported, both in in vitro and in vivo studies as well as in clinical studies (1, 10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, endothelial EVs CD51+ (integrin alpha-V) remained elevated during both exacerbation and remission, thus appearing to be a marker of chronic damage more than endothelial disruption [ 40 ]. Other clinical studies showed that endothelial EVs were significantly increased in the serum of both SPMS and RRMS patients, with higher levels in relapsing–remitting than progressive forms, thus reflecting a status of active peripheral inflammation rather than chronic neurodegeneration [ 42 , 45 , 50 ]. Interestingly, elevated plasma levels of conjugates between endothelial EVs and monocytes directly correlated with MRI gad+ lesions in a court of RRMS patients [ 41 ].…”
Section: Extracellular Vesicles As Potential Biomarkers In Msmentioning
confidence: 99%
“…Pro-inflammatory microenvironment has been also associated to EVs shedding from platelets (glycoprotein Ib alpha chain/CD42b+), significantly increased in plasma of MS patients [ 42 , 47 , 70 ]. Marcos-Ramiro and colleagues isolated platelet EVs and endothelial EVs from the serum of CIS, RRMS and PMS patients and verified their effects on the permeability of a monolayer model of BBB by using trans-endothelial electric resistance (TEER; a measure inversely proportional with barrier permeability) and by confocal analysis.…”
Section: Ev-mediated Blood-brain Barrier Dysfunction and Peripheramentioning
confidence: 99%